Efeito de diferentes métodos mecânicos de limpeza da dentina radicular na resistência de união adesiva de pinos de fibra de vidro - Bortoloto, Alexandre Luís (2021)
The aim of the study was to verify the bond strength through the push-out test using mechanical techniques of 17% EDTA addition to improve the removal of filling materials and smear layer from the prepared space. Bovine teeth (n = 50) were randomly divided into 5 groups: Control (CTRL), Manual (MAN), Conduit Brush (ESCO), EasyClean (EASY) and Passive Ultrasonic Irrigation (PUI), each tooth modeled, filled and preparation to receive the intra-radicular retainer was performed, where we approached the techniques for using the instrument in each group. With the seal cemented, cuts were made in three thirds and the push-out test was performed to verify the breaking strength. The cervical, middle and apical thirds had the highest adhesive bond strength respectively (p <0.001). The EASY and ESCO groups showed better results from the interaction between thirds and the mechanical methods used (p <0.001). The use of Easyclean and Flue Brush in the preparation with 17% EDTA in the flue space brought satisfactory results for the retainer-dentin bond, providing greater bond strength during the push-out test.